Effect of Using Palm Wastes as Additive to Unsaturated Polyester on the Thermal and Acoustic Isolation Properties of a Composite Materials - Mohammed, F.; Shaker, D.; Jalal, N.; Abd, R.; Ali Akber, E. (Anbar Journal of Engineering Sciences, 2018)
The thermal and acoustic isolation properties of unsaturated polyester composites reinforced by palm waste filler have been experimentally investigated. The composites have been prepared using hand lay-up technique with filler weight fraction of (0%, 3%, 5% and 7%). Three types of palm waste that (Date seed, old leaf bases and petiole) were ground and sieved separately to produce the filler with particle size ≤ 400µm. Thermal conductivity, thermal diffusivity, and specific heat capacity were examined using Hot Disk thermal analyses. The acoustic isolation property examined in a sound-insulated box. The experimental results show that the thermal conductivity and thermal diffusivity of the composite specimens reinforced by seed or old leaf bases filler increased with increasing the fillers weight fraction. While increasing the petiole filler decreased the thermal conductivity and thermal diffusivity by 19% and 40% respectively at 5% weight fraction as compared with a pure unsaturated polyester material. So, the composite reinforced with petiole filler has improved the thermal insulation properties. The composites samples reinforced with palm waste show higher sound absorption in compared to the pure unsaturated polyester material. The sound absorption properties of composite reinforced with 7% old leaf bases filler improved by 15% and 23% at low and high frequency respectively rather than of pure unsaturated polyester material.